2016
DOI: 10.1093/bja/aew097
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided radial artery cannulation in adult and paediatric populations: a systematic review and meta-analysis

Abstract: This is the first level one systematic review to demonstrate strong evidence for the use of ultrasound guidance in radial artery cannulation in adult and paediatric populations. In the adult population, ultrasound use significantly increased first-attempt success rate, which subsequently resulted in a significant reduction in the number of attempts. The benefits of ultrasound were also shown in the paediatric population, with a significant increase in first-attempt success rate and reduction in the number of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(54 citation statements)
references
References 17 publications
3
45
1
Order By: Relevance
“…Using US for arterial line placement has proven itself in the perioperative setting 4,8,[13][14][15][16] and in several systematic reviews. 9,[17][18] In one systematic review, Shiloh et al demonstrated that "compared with the palpation method, ultrasound guidance for arterial catheterization was associated with a 71% improvement in the likelihood of first-attempt success. "…”
Section: Discussionmentioning
confidence: 99%
“…Using US for arterial line placement has proven itself in the perioperative setting 4,8,[13][14][15][16] and in several systematic reviews. 9,[17][18] In one systematic review, Shiloh et al demonstrated that "compared with the palpation method, ultrasound guidance for arterial catheterization was associated with a 71% improvement in the likelihood of first-attempt success. "…”
Section: Discussionmentioning
confidence: 99%
“…Data in the literature about the role of US in intravascular AC infections are scarce. The current literature mostly focus only on first-attempt failure, mean attempts to success, mean time to success, and the occurrence of hematoma or venipuncture complications [3][4][5]. Interestingly, all RCTs investigating the role of US for the radial artery in adults assessed only non-infectious complications, thus disregarding intravascular catheter infections [12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…It has revolutionised many areas of critical care including vascular access [1], the trauma survey [2] and point of care diagnositic imaging [3]. Transthoracic echocardiography (TTE) is currently the preferred method in assessing cardiac function and haemodynamic status despite its well-known limitations [4].…”
Section: Commentarymentioning
confidence: 99%